Long‐Term Durability of Transcatheter Aortic Valve Prostheses in Patients With Bicuspid Versus Tricuspid Aortic Valve - Hong‐De Li; Wei‐Ya Li; Jun‐Li Li; Shi‐Qin Peng; Yuan Feng; Yong Peng; Jia‐Fu Wei; Zhen‐Gang Zhao; Tian‐Yuan Xiong; Yuan‐Wei Xiang Ou; Yan Wang; Qing Li; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Currently, there is a lack of evidence for the long‐term bioprosthetic valve durability of patients with bicuspid aortic valve (BAV) following transcatheter aortic valve replacement (TAVR). Methods and Results This study aimed to evaluate hemodynamic outcome, structural valve deterioration, and bioprosthetic valve failure during long‐term follow‐up after TAVR in patients with BAV versus patients with tricuspid aortic valve (TAV). Patients with BAV and TAV who underwent TAVR between 2012 and 2020, with echocardiography followed for at least 3 years, were included. Baseline characteristics, long‐term valve hemodynamic performance, structural valve deterioration, and bioprosthetic valve failure were compared between patients with BAV and TAV. A total of 170 patients with BAV and 145 patients with TAV were included. The mean duration of follow‐up for patients with BAV and TAV was 5.2±1.8 and 5.0±1.7 years. No significant differences were observed in the rates of structural valve deterioration and bioprosthetic valve failure between patients with BAV and TAV: structural valve deterioration, BAV 20 (11.8%) versus TAV 16 (11.0%) at last follow‐up (P=0.861); bioprosthetic valve failure, BAV 3 (1.8%) versus TAV 7 (4.8%) at last follow‐up (P=0.196). More than moderate intravalvular aortic regurgitation (1.8% versus 4.8%, P=0.196) and paravalvular leak (6.5% versus 3.4%, P=0.305) were rare in both patients with BAV and patients with TAV. Conclusions This study indicated satisfactory long‐term valve durability of TAVR in patients with BAV. Comparable hemodynamic outcome, structural valve deterioration, and bioprosthetic valve failure could be achieved in patients with BAV and TAV during long‐term follow‐up after TAVR.